The simplified form of the expression is 3
<h3>Simplifying an Expression</h3>
From the question, we are to simplify the given expression
The given expression is
53 -2(16/8 * 16-7)
Simplifying
Using BODMAS
53 -2(16/8 × 16-7)
53 -2(2 × 16-7)
53 -2(32-7)
53 -2(25)
53 -50
= 3
Hence, the simplified form of the expression is 3
Learn more on Simplifying an Expression here: brainly.com/question/3622770
#SPJ1
Answer:
0(-2+2)=0
Step-by-step explanation:
x=0
x=-2
0(-2+2)=0
<span>the answer issssssssssss, 3713000</span>
Answer:
1/2
Step-by-step explanation:
(1/8+3/12)×(11/6-1/2)
Using bodmas
Deal with the bracket first and it should start with the addition
1/8+3/12
Lcm of the two is 96
12+24/96
=36/96
Then move to the next bracket
11/6-1/2
Lcm is 6
11-3/6
=8/6
Bring the two answers together
36/96×8/6
=1/2